1985
DOI: 10.1159/000176992
|View full text |Cite
|
Sign up to set email alerts
|

Fed and Fasting Thermoregulation in ob/ob Mice

Abstract: The body temperatures of mature lean and obese C57BL/6J mice were measured just after feeding, during ad libitum access to food, or every 24 h throughout a 3-day fast. Obese mice had body temperatures 1.0–1.4 °C lower than lean mice in the postprandial state and during ad libitum feeding. During food deprivation, obese mice became more hypothermic than lean sex-matched controls. A 5 °C fall in body temperature was observed in mutant females in the first 24 h of starvation, about twice that seen in any other ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…Since HCRs 433 have more OXPHOS proteins and higher UCP2 and PGC-1 levels in skeletal muscle, it may 434 be speculated that the higher proton leakage may also be one reason for HCRs higher 435 thermogenesis. On the other hand, several animal models have demonstrated that rodents 436 with inherited obesity have low body temperatures , Trayhurn, 437 Thurlby & James 1977, Dubuc, Wilden & Carlisle 1985. Here we show for the first time, 438 that similarly to inherited obesity, LCRs have lower body temperature than HCRs, and are 439 prone to gain excess weight and develop metabolic disorders (Noland et al 2007, Koch & 440 Britton 2005, Kivelä et al 2010).…”
Section: Voluntary Running Aids To Maintain High Thermo-genesis Inmentioning
confidence: 59%
See 1 more Smart Citation
“…Since HCRs 433 have more OXPHOS proteins and higher UCP2 and PGC-1 levels in skeletal muscle, it may 434 be speculated that the higher proton leakage may also be one reason for HCRs higher 435 thermogenesis. On the other hand, several animal models have demonstrated that rodents 436 with inherited obesity have low body temperatures , Trayhurn, 437 Thurlby & James 1977, Dubuc, Wilden & Carlisle 1985. Here we show for the first time, 438 that similarly to inherited obesity, LCRs have lower body temperature than HCRs, and are 439 prone to gain excess weight and develop metabolic disorders (Noland et al 2007, Koch & 440 Britton 2005, Kivelä et al 2010).…”
Section: Voluntary Running Aids To Maintain High Thermo-genesis Inmentioning
confidence: 59%
“…Yet it 544 remains controversial whether high body temperature and high rate of metabolism are 545 beneficial to health and longevity. However, since there is clear evidence of obese animals 546 having low body temperatures , Trayhurn, Thurlby & James 547 1977, Dubuc, Wilden & Carlisle 1985, it would be worth studying the potential role of 548 intrinsically low body temperature at the onset of obesity in humans. 549…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that female C57Bl mice drop their body temperature more than males when fasted (9), but the reasons were not identified. When food was restricted in the present studies, female mice reduced thermogenesis more effectively than males (compare Fig.…”
Section: Discussionmentioning
confidence: 97%
“…7 The literature abounds with information about effects of fasting on factors of energetics other than body mass such as body core temperature and spontaneous locomotor activity in normal mice. 8,9,10,11 In several other homeotherm species, such as pigeons and rats, it has been observed that body temperature of food-deprived animals becomes progressively lower on the consecutive days in the inactive phase of the day, whereas body core temperature remains normal in the active phase. 12,13 During fasting, small endotherms may employ daily torpor, a suppression of metabolic rate to as low as 30% of basal metabolic rate together with a fall of core temperature lasting for a period of several hours.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the probably hyperleptinemic obese mice of the present study, in leptindeficient ob/ob mice food deprivation can induce daily torpor shortly after the start of fasting; moreover, obese mice become more hypothermic than the lean sex-matched controls. 8 It has not been clear so far if the fall of the whole body mass or the fall of fat tissue mass could be the regulatory factor serving as a signal to allow progressive hypothermia. Conversely, metabolically active tissue mass decreasing to some critically low level could limit the availability of substrate(s) needed as fuel for brain energy metabolisms which finally may lead to severe hypothermia.…”
mentioning
confidence: 99%